2014
DOI: 10.1016/j.fob.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy induces retinal pigment epithelial cell damage by the lipofuscin fluorophore A2E

Abstract: HighlightsAutophagy was augmented in RPE cells in the presence of a lipofuscin pigment, A2E.RPE cell death was induced in the presence of A2E with an autophagy inhibitor.Inhibition of autophagy resulted in the accumulation of abnormal mitochondria.Autophagy in RPE cells prevents the accumulation of damaged cellular molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…A study by Saadat et al observed that blocking autophagy greatly increased A2E-induced cell death in ARPE-19 cells (20). Interestingly, genes involved in both autophagy and apoptosis such as CASP3, DRAM1 and PERK were up-regulated after A2E incubation in our gene array.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A study by Saadat et al observed that blocking autophagy greatly increased A2E-induced cell death in ARPE-19 cells (20). Interestingly, genes involved in both autophagy and apoptosis such as CASP3, DRAM1 and PERK were up-regulated after A2E incubation in our gene array.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, cellular stressors in the eye, such as A2E accumulation, reactive oxygen species production and mitochondrial dysfunction can increase autophagy (20,21). Autophagic activity has also been observed to follow a cyclic pattern similar to the daily rhythm of POS phagocytosis detected in RPE cells; this suggests a role for autophagy in retinoid recycling and daily maintenance of photoreceptors (2,22).…”
Section: Autophagy Is An Evolutionarily Conserved Catabolic Mechanismmentioning
confidence: 86%
“…This is consistent with Janet R. Sparrow's research [29,30] and close to the research on human donors' eyes [31] . In recent years, a lot of research has proved that A2E not only induces the photodamage of RPE cells [32][33][34][35] , but also causes inflammation [36][37][38][39] , and these are the major risk factors of retinal degenerative disease. Therefore, the blue light-induced A2E-containing RPE cell damage model we have established is a proper in vitro model for investigating the pathological changes of retinal degenerative disease.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo deletion of autophagic gene RB1CC1 in mouse retina results in retinal degeneration that shares many features with AMD disease [109]. RPE cells in vitro accumulate lipofuscin and greater loss of mitochondrial activity and membrane integrity under oxidative stress when autophagy is inhibited [13,125,203]. Autofluorescent lipofuscin in the RPE destabilizes the lysosome and is a hallmark of RPE senescence that has been widely implicated in AMD [204,205].…”
Section: Retinamentioning
confidence: 99%
“…Autophagy plays a critical role in controlling NLRP3 inflammasome activity in the retina. Several in vitro experiments show dramatic upregulation of inflammasome activity in RPE and secretion of IL-1β after autophagic flux inhibition [139][140][141] [203]. Wortmannin inhibits autophagy by inhibiting class III PI3Kinase [241].…”
Section: Non-canonical Lc3 Associatedmentioning
confidence: 99%